2017
DOI: 10.3390/f8010025
|View full text |Cite
|
Sign up to set email alerts
|

Using Fractal Analysis in Modeling the Dynamics of Forest Areas and Economic Impact Assessment: Maramureș County, Romania, as a Case Study

Abstract: Abstract:This study uses fractal analysis to quantify the spatial changes of forest resources caused by an increase of deforested areas. The method introduced contributes to the evaluation of forest resources being under significant pressure from anthropogenic activities. The pressure on the forest resources has been analyzed for Maramures , County, one of the most deforested counties in Romania. In order to evaluate this, the deforested areas were calculated for the period of 2001-2014, by using the Global Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 29 publications
1
49
0
Order By: Relevance
“…Our results add new insights to forest cover change as compared to previous studies based on fractal analysis [3,11,13,[36][37][38]. The findings of this study clearly confirmed the hypothesis that fractal analysis can provide an interesting new way of quantifying the degree of fragmentation and organization of forest areas characterized by deforestation and reforestation.…”
Section: Usage Of Fractal Analysis For Quantification Of Forest Changessupporting
confidence: 86%
See 2 more Smart Citations
“…Our results add new insights to forest cover change as compared to previous studies based on fractal analysis [3,11,13,[36][37][38]. The findings of this study clearly confirmed the hypothesis that fractal analysis can provide an interesting new way of quantifying the degree of fragmentation and organization of forest areas characterized by deforestation and reforestation.…”
Section: Usage Of Fractal Analysis For Quantification Of Forest Changessupporting
confidence: 86%
“…In previous studies, fractal analysis of forest areas was determined by using the Fractal Fragmentation Index [13,36] or Minkowski Dimension and Pyramid Dimension [33]. Until now, the dilation method was used to evaluate the quality of the commune or urban built-up areas [44] and we clarified the importance of utilizing the dilation method in understanding the textural organization of forest areas and the effects generated by deforestation and reforestation.…”
Section: Usage Of Fractal Analysis For Quantification Of Forest Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the deforestation patterns from satellite images through fractal analysis is expected to facilitate the development of a method, together with other well-known fractal methods and may provide valuable complementary information to currently available methodologies in the field of forestry research. The results of deforestation patterns in Moldo-Transylvanian Carpathians, based on Landsat ETM+ analysis [31,46], was performed for the period 2000-2014 using fractal indexes: FFI, ΛT-o-W and different fractal dimensions. Computation with the ImageJ program allowed for the determination of fractal dimensions for deforested areas and the maps generated from four case studies showed different spatiotemporal deforestation patterns of forests from the mountain area of Moldo-Transylvanian Carpathians.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past years the Metropolitan Areas met with issues regarding urban population growth, uses of land, change of land coverage (Cîmpianu and Ema 2013), habitat fragmentation, deforestation , Draghici et al 2017) and loss of natural vegetation (Grigorescu and Geacu, 2017, Geacu et all. 2012, Ionus et al 2011.…”
Section: Introductionmentioning
confidence: 99%